Dynamic state variable models in ecology : methods and applications - Clark, Colin Whitcomb, 1931- (Oxford series in ecology and evolution., 2000)
1. The Basics. 2. Some Details of Technique. 3. Using the Model. 4. Oviposition Behavior of Insect Parasitoids. 5. Winter Survival Strategies. 6. Avian Migration. 7. Human Behavioral Ecology. 8. Conservation Biology. 9. Agroecology. 10. Population-Level Models. 11. Stochasticity, Uncertainty, and Information as a State Variable. 12. Measures of Fitness. Appendix: Programs Available at the OUP Web Site. References. Index.